2024
DOI: 10.1002/agj2.21526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of manure injection on spatial variability in soil nitrate, carbon, and small grain growth

Derek R. Hilfiker,
Rory O. Maguire,
Gonzalo Ferreira
et al.

Abstract: Manure injection alters the spatial distribution of manure by concentrating it in a subsurface band which can lead to differential soil nutrient distribution and growth in small grains. This study assessed the effects of fall manure applications on soil NO3‐N, active carbon, and small grain growth compared to broadcasting and a no manure control. Soil samples were taken to represent whole plot soil means for all treatments, while in‐band (IB) and between‐band (BB) soil samples were taken in injected plots to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 63 publications
5
2
0
Order By: Relevance
“…Furthermore, no differences in soil NO 3 -N were observed at silage harvest, indicating that elevated soil N levels were not present to drive a change if N did limit maturity. These results are similar to Hilfiker et al (2023a), who found no differences in-band compared to between-band small grain growth stage at silage harvest. No other studies have examined differential maturity in small grains under injection, and the data presented in this study provides the first evidence that fall dairy manure injection does not lead to differential maturity at silage harvest time.…”
Section: Small Grain Growth Stagesupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, no differences in soil NO 3 -N were observed at silage harvest, indicating that elevated soil N levels were not present to drive a change if N did limit maturity. These results are similar to Hilfiker et al (2023a), who found no differences in-band compared to between-band small grain growth stage at silage harvest. No other studies have examined differential maturity in small grains under injection, and the data presented in this study provides the first evidence that fall dairy manure injection does not lead to differential maturity at silage harvest time.…”
Section: Small Grain Growth Stagesupporting
confidence: 90%
“…As N would likely be the primary driver of increases observed in-band versus between-band, the lack of differences in CP provides further evidence that the increased early season concentration of NO 3 -N in the injection band did not cause increased in-band forage nutritive value to be observed by silage harvest. These results are similar to Hilfiker et al (2023a), who found no changes in CP across 2 years and small grain species at silage harvest when comparing in-band to between-band samples. As with CP, the other forage nutritive value parameters were rarely elevated in-band, with ADL showing significant in-band elevation at two sites, and NDF, IVDMD, and sugars showing in-band elevation at one site each (p < 0.05).…”
Section: Small Grain Forage Nutritive Valuesupporting
confidence: 89%
See 3 more Smart Citations